Sequential Biorefining of Bioactive Compounds of High Functional Value from Calafate Pomace (Berberis microphylla) Using Supercritical CO2 and Pressurized Liquids - Jaime Ortiz-Viedma; José M. Bastias-Montes; Cielo Char; Camila Vega; Alejandra Quintriqueo; Manuela Gallón-Bedoya; Marcos Flores; José M. Aguilera; José M. Miranda; Jorge Barros-Velázquez (MDPI AG, 2023)
A biorefinery process was developed for a freeze-dried pomace of calafate berries (Berberis microphylla). The process consisted of extraction of lipophilic components with supercritical CO2 (scCO2) and subsequent extraction of the residue with a pressurized mixture of ethanol/water (1:1 v/v). scCO2 extracted oil from the pomace, while pressurized liquid extraction generated a crude extract rich in phenols and a residue rich in fiber, proteins and minerals. Response surface analysis of scCO2 extraction suggested optimal conditions of 60 °C, 358.5 bar and 144.6 min to obtain a lipid extract yield of 11.15% (d.w.). The dark yellow oil extract contained a good ratio of ω6/ω3 fatty acids (1:1.2), provitamin E tocopherols (406.6 mg/kg), and a peroxide index of 8.6 meq O2/kg. Pressurized liquid extraction generated a polar extract with good phenolic content (33 mg gallic acid equivalents /g d.w.), anthocyanins (8 mg/g) and antioxidant capacity (2,2-diphenyl-1-picrylhydrazyl test = 25 µg/mL and antioxidant activity = 63 µM Te/g). The extraction kinetics of oil by scCO2 and phenolic compounds were optimally adjusted to the spline model (R2 = 0.989 and R2 = 0.999, respectively). The solid extracted residue presented a fiber content close to cereals (56.4% d.w.) and acceptable values of proteins (29.6% d.w.) and minerals (14.1% d.w.). These eco-friendly processes valorize calafate pomace as a source of ingredients for formulation of healthy foods, nutraceuticals and nutritional supplements.